Role of Chemokines in Thyroid Cancer Microenvironment: Is CXCL8 the Main Player? - Rotondi, Mario; Coperchini, Francesca; Latrofa, Francesco; Chiovato, Luca (Frontiers in Endocrinology, 2018)
Tumor-related-inflammation does influence the biological behavior of neoplastic cells and ultimately the patient’s outcome. With specific regard to thyroid cancer, the issue of tumor-associated inflammation has been extensively studied and recently reviewed. However, the role of chemokines, which play a crucial role in determining the immuno-phenotype of tumor-related-inflammation, was not addressed in previous reviews on the topic. Experimental evidence shows that thyroid cancer cells actively secrete a wide spectrum of chemokines and, at least for some of them, solid scientific data support a role for these immune-active molecules in the aggressive behavior of the tumor. Our proposal for a review article on chemokines and thyroid cancer stems from the notion that chemokines, besides having the ability to attract and maintain immune cells at the tumor site, also produce several pro-tumorigenic actions, which include pro-angiogenetic, cyto-proliferative and pro-metastatic effects. Studies taking into account the role of CCL15, CXCL12, CXCL16, CXCL1, CCL20 and CCL2 in the context of thyroid cancer will be reviewed with particular emphasis on CXCL8. The reason for focusing on CXCL8 is that this chemokine is the most studied one in human malignancies, displaying multi-faced pro-tumorigenic effects. These include enhancement of tumor cells growth, metastatization and angiogenesis overall contributing to the progression of several cancers including thyroid cancer. We aim at reviewing current knowledge on the: i) ability of both normal and tumor thyroid cells to secrete CXCL8; ii) direct/indirect pro-tumorigenic effects of CXCL8 demonstrated by in vitro and in vivo studies specifically performed on thyroid cancer cells; iii) pharmacologic strategies proven to be effective for lowering CXCL8 secretion and/or its effects on thyroid cancer cells.